Assessment of the Effects of Aerobic Fitness on Cerebrovascular Function in Young Adults Using Multiple Inversion Time Arterial Spin Labeling MRI - Foster, Catherine; Steventon, Jessica J.; Helme, Daniel; Tomassini, Valentina; Wise, Richard G. (Frontiers in Physiology, 2020)
This cross-sectional study investigated the effects of aerobic fitness on cerebrovascular function in the healthy brain. Grey matter cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) were quantified in a sample of young adults within a normal fitness range. Based on existing Transcranial Doppler ultrasound and fMRI evidence, a positive relationship between fitness and resting grey matter CBF, and CVR was predicted. Exploratory hypotheses that higher V ̇O2peak would be associated with higher GM volume and cognitive performance were also investigated. 20 adults underwent a V ̇O2peak test and a battery of cognitive tests. All subjects also underwent an MRI scan where multiple inversion time (MTI) pulsed arterial spin labelling (PASL) was used to quantify resting CBF and CVR to 5% CO2. Region of interest analysis showed a non-significant inverse correlation between whole-brain grey matter CBF and V ̇O2peak; r=-0.4, p=0.08, corrected p (p’) =0.16 and a significant positive correlation between V ̇O2peak and whole-brain averaged grey matter CVR; r=0.62, p=0.003, p’ =0.006. Voxel-wise analysis revealed a significant inverse association between V ̇O2peak and resting CBF in the left and right thalamus, brainstem, right lateral occipital cortex, left intra-calcarine cortex and cerebellum. The results of this study suggest that aerobic fitness is associated with lower CBF and greater CVR in young adults.